فعالية استخدام لعبة الكلمات المسلسلة لتعليم مهارة الكلام في الصف العاشر بالمدرسة الثانوية المنار فرامبون عانجوك: Efektivitas Penggunaan Permainan Kata Berantai untuk Pengajaran Keterampilan Bicara di Kelas X MA Al-Manar Prambon Nganjuk - Zuhriyah, Nunik; Hasyim, Muhammad (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Speaking Arabic is one of the four skills that must be learned to master Arabic, which contains five elements, namely: speech, vocabulary, rhetoric, fluency, understanding. To make learning easier, researchers use a series of sentence games, because students tend to easily spread things in a fun way.The use of stringed sentence game methods in the learning of speech skills in class X MA Al Manar, aims to learn the results of the application of methods used in learning as well as expected students to be able to apply speaking skills in activities in the classroom using stringed games. The researchers used quantitative research methods, with data collection methods followed by observations, interviews, tests and documentation to find out the effectiveness of the use of string sentence games in Arabic language learning, especially speech skills.After the research process for six meetings in class X MIPA Al Manar Prambon Nganjuk, using the method of a series of sentence game. The test results showed the student's T score count: 6,759, while the T score Table: 2.080 shows the effectiveness of the use of this stringed sentence game.